E. coli-expressed SECRET AGENT O-GlcNAc modifies threonine 829 of GIGANTEA - Kim, Young-Cheon; Hartweck, Lynn M.; Olszewski, Neil E. (Frontiers in Plant Science, 2024)
The Arabidopsis thaliana glycosyl transferases SPINDLY (SPY) and SECRET AGENT (SEC) modify nuclear and cytosolic protein with O-linked fucose or O-linked N-acetylglucosamine (O-GlcNAc), respectively. O-fucose and O-GlcNAc modifications can occur at the same sites. SPY interacts physically and genetically with GIGANTEA (GI) suggesting it may be modified by both enzymes. Previously, we found that when co-expressed in E. coli SEC modifies GI, however, the modification site was not determined. By analyzing overlapping sub-fragments of GI, we identified a region that was modified by SEC in E. coli. Modification was undetectable when threonine 829 (T829) was mutated to alanine while the T834A and T837A mutations reduced modification suggesting that T829 was the primary or only modification site. Mapping using mass spectrometry detected only modification of T829. Previous studies have shown that positions modified by SEC in E. coli are modified in planta suggesting that T829 is O-GlcNAc modified in planta.